2010
DOI: 10.1021/jp103173d
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron Imaging and Spectroscopy of MI2 (M = Cs, Cu, Au): Evolution from Ionic to Covalent Bonding

Abstract: We report a combined experimental and theoretical investigation of MI(2)(-) (M = Cs, Cu, Ag, Au) to explore the chemical bonding in the group IA and IB diiodide complexes. Both photoelectron imaging and low-temperature photoelectron spectroscopy are applied to MI(2)(-) (M = Cs, Cu, Au), yielding vibrationally resolved spectra for CuI(2)(-) and AuI(2)(-) and accurate electron affinities, 4.52 ± 0.02, 4.256 ± 0.010, and 4.226 ± 0.010 eV for CsI(2), CuI(2), and AuI(2), respectively. Spin-orbit coupling is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 53 publications
6
43
0
Order By: Relevance
“…Single-point CCSD(T) energies of the ground and excited states of UO 2 Cl 4 − were calculated at the optimized SR-CCSD(T) geometry of UO 2 Cl 4 2− , generating accurate state-specific SR energies for all the states. The electron detachment energies corresponding to one-electron transitions from the closed-shell ground state of UO 2 Cl 4 2− to the ground and excited states of UO 2 Cl 4 − were obtained using the CASSCF/CCSD(T)/SO approach, 17,[45][46][47][48] which has been shown to generate accurate excitation energies for molecules containing heavy elements. 17,32,49 In this approach, the SO splittings were treated as a perturbation to the SR state energies and were calculated on the basis of CASSCF wavefunctions with the diagonal matrix elements replaced by the individual CCSD(T) state energies.…”
Section: B Theoretical and Computational Methodsmentioning
confidence: 99%
“…Single-point CCSD(T) energies of the ground and excited states of UO 2 Cl 4 − were calculated at the optimized SR-CCSD(T) geometry of UO 2 Cl 4 2− , generating accurate state-specific SR energies for all the states. The electron detachment energies corresponding to one-electron transitions from the closed-shell ground state of UO 2 Cl 4 2− to the ground and excited states of UO 2 Cl 4 − were obtained using the CASSCF/CCSD(T)/SO approach, 17,[45][46][47][48] which has been shown to generate accurate excitation energies for molecules containing heavy elements. 17,32,49 In this approach, the SO splittings were treated as a perturbation to the SR state energies and were calculated on the basis of CASSCF wavefunctions with the diagonal matrix elements replaced by the individual CCSD(T) state energies.…”
Section: B Theoretical and Computational Methodsmentioning
confidence: 99%
“…However, the latter analysis is basisdependent and it is commonly known that one should be cautious when using it especially for atoms with significant overlaps of atomic orbitals [32]. Recently, Wang et al reported an analysis of the bonding in small copper and gold halide complexes, and found a significant covalent character in the metal-halide bonds [33,34].…”
Section: Characterization Of the Iono-covalent Bondingmentioning
confidence: 99%
“…Vibrationally resolved spectra were obtained for the AuH and Au 2 H species, thus demonstrating the usefulness of the technique. MI 2 species (M = Cs, Cu, and Au) have also been investigated using VMI by Wang et al, 22 also in 2010. The images of AuI 2 and CuI 2 gave well-defined vibrational structure and thus could be examined at a high level of detail.…”
Section: Introductionmentioning
confidence: 99%